Free amino acids in the Arctic snow and ice core samples: Potential markers for paleoclimatic studies - BARBARO, ELENA; Spolaor, Andrea; KARROCA, ORNELA; Park, Ki Tae; Martma, Tõnu; Isaksson, Elisabeth; Kohler, Jack; Gallet, Jean Charles; Bjorkman, Mats P; Cappelletti, David; Spreen, Gunnar; ZANGRANDO, Roberta; et al. (Science of The Total Environment, 2017)
The role of oceanic primary production on climate variability has long been debated. Defining changes in past oceanic primary production can help understanding of the important role that marine algae have in climate variability. In ice core research methanesulfonic acid is the chemical marker commonly used for assessing changes in past primary production. However, other organic compounds such as amino acids, can be produced and emitted into the atmosphere during a phytoplankton bloom. These species can be transported and deposited onto the ice cap in polar regions. Here we investigate the correlation between the concentration of chlorophyll-a, marker of marine primary production, and amino acids present in an ice core. For the first time, free l- and d-amino acids in Arctic snow and firn samples were determined by a sensitive and selective analytical method based on liquid chromatography coupled with tandem mass spectrometry. The new method for the determination of free amino acids concentrations was applied to firn core samples collected on April 2015 from the summit of the Holtedahlfonna glacier, Svalbard (N 79'08.424, E 13'23.639, 1120m a.s.l.). The main results of this work are summarized as follows: (1) glycine, alanine and proline, were detected and quantified in the firn core samples; (2) their concentration profiles, compared with that of the stable isotope δ(18)O ratio, show a seasonal cycling with the highest concentrations during the spring and summer time; (3) back-trajectories and Greenland Sea chlorophyll-a concentrations obtained by satellite measurements were compared with the amino acids profile obtained from ice core samples, this provided further insights into the present results. This study suggests that the amino acid concentrations in the ice samples collected from the Holtedahlfonna glaciers could reflect changes in oceanic phytoplankton abundance. The role of oceanic primary production on climate variability has long been debated. Defining changes in past oceanic primary production can ...